Evaluating biases in sea surface temperature records using coastal weather stations - Cowtan, Kevin; Rohde, Robert; Hausfather, Zeke (Quarterly journal of the Royal Meteorological Society, 2018)
Sea surface temperatures form a vital part of global mean surface temperature records. Historical observation methods have changed substantially over time from buckets to engine‐room intake sensors, hull sensors and drifting buoys, rendering their use for climatological studies problematic. There are substantial uncertainties in the relative biases of different observations which may impact the global temperature record. Island and coastal weather stations can be compared to coastal sea surface temperature observations to obtain an assessment of changes in bias over time. The process is made more challenging by differences in the rate of warming between air temperatures and sea surface temperatures, and differences across coastal boundaries. A preliminary sea surface temperature reconstruction homogenized using coastal weather station data suggests significant changes to the sea surface temperature record, although there are substantial uncertainties, only some of which can be quantified. A large warm excursion in versions 4 and 5 of the NOAA Extended Reconstructed Sea Surface Temperature during World War 2 is rejected, as is a cool excursion around 1910 present in all existing records. The mid‐century plateau is cooler than in existing reconstructions. Sea surface temperature observations are subject to significant biases, particularly around World War 2 when there was a shift from measuring water collected in a bucket on deck to water from engine‐room intakes. The HadSST3 dataset corrects this bias using metadata about the observation method. We make an empirical estimate of the bias from the difference between nearby ship and land temperature readings. The results are similar for World War 2, but show significant differences for other periods.